Prevalence and Analysis of Medical Device-Related Pressure Injuries: Results from the International Pressure Ulcer Prevalence Survey. (June 2018) - Kayser, Susan A.; VanGilder, Catherine A.; Ayello, Elizabeth A.; Lachenbruch, Charlie
ABSTRACT: OBJECTIVE: To examine the prevalence and characteristics of medical device–related pressure injuries (MDR PIs) in a large, generalizable database. METHODS: This study is a retrospective analysis of the 2016 International Pressure Ulcer Prevalence data. Data were limited to US and Canadian facilities. Facilities included acute care, long-term care, rehabilitation, long-term acute care hospitals, and hospice. Analysis included 102, 865 adult patients; 99, 876 had complete data and were the focus of the analysis and are reported in the results below. RESULTS: The overall PI prevalence was 7.2% (n = 7189), and the facility-acquired prevalence was 3.1% (n = 3113). The prevalence of MDR PIs was 0.60% (n = 601), which included both mucosal and nonmucosal MDR PIs. In this study, 75% of MDR PIs were facility acquired, whereas non-MDR PIs were most commonly present on admission. Facility-acquired MDR PIs formed 3 days faster than facility-acquired non-MDR PIs (12 vs 15 days; P < .05). By stage, most MDR PIs were superficial (58% were Stage 1 or 2), 15% were deep-tissue PIs, and 22% were full-thickness PIs (Stage 3 or 4 or unstageable). The most common anatomic locations for MDR PIs were the ears (29%) and the feet (12%). The most common devices associated with MDR PIs were nasal oxygen tubes, 26%; other, 19%; cast/splints, 12%; and continuous positive airway pressure/bilevel positive airway pressure masks, 9%. CONCLUSIONS: Because MDR PIs form faster than non-MDR PIs, timely proactive assessment and prevention measures are critical. Most MDR PIs occurred at the face and head region, and the ears specifically. The most common devices linked with MDR PIs were oxygen tubing and masks, making assessment and prevention efforts critical for patients who require those devices.